Erythrocyte Membrane‐Coated Invisible Acoustic‐Sensitive Nanoparticle for Inducing Tumor Thrombotic Infarction by Precisely Damaging Tumor Vascular Endothelium. Issue 30 (5th July 2022) - Xie, Huichao; Li, Wan; Liu, Hui; Chen, Yongfeng; Ma, Mengrui; Wang, Yichen; Luo, Yucen; Song, Di; Hou, Qianqian; Lu, Wenwen; Bai, Yu; Li, Bao; et al.
Abstract: Selective induction of tumor thrombus infarction is a promising antitumor strategy. Non‐persistent embolism due to non‐compacted thrombus and activated fibrinolytic system within the tumor large blood vessels and tumor margin recurrence are the main therapeutic bottlenecks. Herein, an erythrocyte membrane‐coated invisible acoustic‐sensitive nanoparticle (TXA+DOX/PFH/RBCM@cRGD) is described, which can induce tumor thrombus infarction by precisely damaging tumor vascular endothelium. It is revealed that TXA+DOX/PFH/RBCM@cRGD can effectively accumulate on the endothelial surface of tumor vessels with the help of the red blood cell membrane (RBCM) stealth coating and RGD cyclic peptide (cRGD), which can be delivered in a targeted manner as nanoparticle missiles. As a kind of phase‐change material, perfluorohexane (PFH) nanodroplets possess excellent acoustic responsiveness. Acoustic‐sensitive missiles can undergo an acoustic phase transition and intense cavitation with response to low‐intensity focused ultrasound (LIFU), damaging the tumor vascular endothelium, rapidly initiating the coagulation cascade, and forming thromboembolism in the tumor vessels. The drugs loaded in the inner water phase are released explosively. Tranexamic acid (TXA) inhibits the fibrinolytic system, and doxorubicin (DOX) eliminates the margin survival. In summary, a stealthy and acoustically responsive multifunctional nanoparticle delivery platform is successfully developed for inducing thrombus infarction by precisely damaging tumor vascular endothelium. Abstract : Erythrocyte membrane‐coated invisible acoustic‐sensitive nanoparticles can respond to low‐intensity focused ultrasound (LIFU) radiation, undergo acoustic phase change and intense cavitation, precisely disrupt the tumor vascular endothelium, and then induce tumor thrombotic infarction through a dual mechanism of action of "coagulation initiation‐fibrinolysis inhibition". The tumor margins are simultaneously destroyed efficiently, and the rapidly growing tumor is completely contained.